The implosion of Transkei and Ciskei - Peires, J.B. (My University, 1992)
The South African government’s policy of granting "independence" to the black reserves within its borders evoked considerable initial interest, particularly with regard to Transkei, the first black territory to be so blessed. Liberal writers approached the so-called "homelands" with sympathy, giving serious consideration to their possible viability, and exploring their potential as an engine for future change. Three well-known American academics went so far as to dub Transkei as ‘virtually the only ground where Africans can voice non-violent opposition to (the South African) regime’…. It is naturally impossible for me to give a comprehensive account of the entire collapse within the limits of a single paper. My object is the more modest one of relating the hitherto uncompiled history of the Transkei and Ciskei 'independent' homelands which spearheaded the process. By implosion, I do not mean to denote a catastrophe of literally astrophysical proportions. I merely use the word to imply comparison with the physical process whereby a weakness at the centre is unable to support the outer facade of a structure and results in its inward collapse. The weakness at the centre may be found in the disjuncture between the homeland leadership and the homeland bourgeoisie, who might have constituted their local class base. I will return to this subject in my conclusion.
African Studies Seminar series. Paper presented 4 May 1992
Keywords: Transkei (South Africa). Politics and government; Ciskei (South Africa). Politics and government